2020
DOI: 10.1371/journal.pone.0239217
|View full text |Cite
|
Sign up to set email alerts
|

Temporal variation in food consumption of Brazilian adolescents (2009-2015)

Abstract: Background Worldwide population has been increasingly exposed to ultra-processed foods, which are associated with obesity. Adolescence is a transition period of life and WHO recommends the surveillance of risk factors to the adolescents’ health, such as diet, because experiences in this phase can result in health risks. Objective To assess the trends in food consumption of adolescents from Brazilian capitals according to sociodemographic variables, based on data from th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 22 publications
1
9
0
Order By: Relevance
“…Accordingly, significant Fe intake differences over time were more pronounced among women from the wealthiest Brazilian regions (southeast and southern) relative to those from the poorest regions (north and northeast). Possible explanations for these results might be related to previously described sociodemographic disparities in the nutritional transition-related trends of substituting traditional staple Brazilian foods, such as rice and beans, for more convenient alternative items, such as ready-to-eat and ultra-processed products (34)(35)(36) . In fact, studies with adolescent students and adults from capital cities suggest that the frequency of regular consumption of beans (≥ 5 times/week) over the last decade declined mainly among women compared with men (-3•6 % v. -2•9 %/year between 2009 and 2015 (35) and -1•4 % v. -1•2 %/year between 2012 and 2017 (36) , respectively).…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…Accordingly, significant Fe intake differences over time were more pronounced among women from the wealthiest Brazilian regions (southeast and southern) relative to those from the poorest regions (north and northeast). Possible explanations for these results might be related to previously described sociodemographic disparities in the nutritional transition-related trends of substituting traditional staple Brazilian foods, such as rice and beans, for more convenient alternative items, such as ready-to-eat and ultra-processed products (34)(35)(36) . In fact, studies with adolescent students and adults from capital cities suggest that the frequency of regular consumption of beans (≥ 5 times/week) over the last decade declined mainly among women compared with men (-3•6 % v. -2•9 %/year between 2009 and 2015 (35) and -1•4 % v. -1•2 %/year between 2012 and 2017 (36) , respectively).…”
Section: Discussionmentioning
confidence: 90%
“…Possible explanations for these results might be related to previously described sociodemographic disparities in the nutritional transition-related trends of substituting traditional staple Brazilian foods, such as rice and beans, for more convenient alternative items, such as ready-to-eat and ultra-processed products (34)(35)(36) . In fact, studies with adolescent students and adults from capital cities suggest that the frequency of regular consumption of beans (≥ 5 times/week) over the last decade declined mainly among women compared with men (-3•6 % v. -2•9 %/year between 2009 and 2015 (35) and -1•4 % v. -1•2 %/year between 2012 and 2017 (36) , respectively). In turn, data from the NDS-HBS indicated that decreasing trends between 2008-2009 and 2017-2018 in the frequency of consumption of rice (-9•4 %) and breads (-19•2 %) were especially pronounced among individuals with a family income above two minimum wages per capita (-16•0 % and -28•1 %, respectively) (14,31) .…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…In Brazil, unhealthy eating habits showed a significant increase, especially among adolescents from low-income families 27 . The consumption of ultra-processed foods has increased at the expense of unprocessed foods such as rice, beans, and fruits, although sugary drinks' intake has decreased in the last decade 28,29 . A similar decreasing trend in the consumption of sugary drinks was found in the USA among children and adolescents 30,31 .…”
Section: Discussionmentioning
confidence: 99%
“…Much of the increase in the prevalence of metabolic diseases in Brazil is attributed to an epidemiological transition characterised by changes in Brazilian age structure, population ageing, reduced rates of infant mortality and fertility and increased low birth weight [15][16][17][18][19]. Changes in the cultural and socioeconomic patterns, for instance, increasing urbanisation and economic improvement, have led to negative changes in lifestyle behaviours, including physical inactivity and unhealthy diet, in the Brazilian adolescent/ young adult population [20]. A previous study has shown that the intake of saturated fatty acids (SFA) was higher in adolescents than adults in Brazil [21].…”
Section: Introductionmentioning
confidence: 99%